2005
DOI: 10.1016/j.euje.2005.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Early impairment of myocardial function in systemic sclerosis: Non-invasive assessment by Doppler myocardial and strain rate imaging

Abstract: Pulsed DMI and SRI are valuable non-invasive and easy-repeatable tools for detecting RV and LV myocardial involvement caused by SSc, and may therefore be useful to early identify patients with more diffused and severe form of SSc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(38 citation statements)
references
References 35 publications
3
34
0
1
Order By: Relevance
“…Recent studies in SSc patients based on TDE showed both systolic and diastolic right ventricle dysfunction [6, 7]. We showed impaired right ventricle systolic function in the patients with elevated RVSP as compared to the patients with normal pulmonary pressure.…”
Section: Discussionsupporting
confidence: 50%
“…Recent studies in SSc patients based on TDE showed both systolic and diastolic right ventricle dysfunction [6, 7]. We showed impaired right ventricle systolic function in the patients with elevated RVSP as compared to the patients with normal pulmonary pressure.…”
Section: Discussionsupporting
confidence: 50%
“…D’Andrea et al1,43 found an independent negative correlation between right ventricular early myocardial (Em) peak velocity, Rodnan skin score and anti-SCL70 antibodies. Nakajima et al44 found a significant positive correlation between ventricular diastolic dysfunction and worsening of skin sclerosis.…”
Section: Discussionmentioning
confidence: 97%
“…Mele et al showed that TDI-derived myocardial systolic deformation indices, based on strain and strain rate analysis and E/e’ ratio, are a valuable approach to detecting cardiac involvement in asymptomatic SSc patients [35]. D’Andrea et al further confirmed that STE imaging can detect both RV and LV early myocardial involvement in SSc, as well as coronary flow reserve and brachial artery flow-mediated dilatation, as signs of early vascular impairment [53]. In another study, Shattke et al employed isovolumetric acceleration, a novel tissue Doppler parameter, to detect early RV systolic impairment in SSc patients without pulmonary hypertension [51].…”
Section: Discussionmentioning
confidence: 99%